Characterization of monoolein-based lipoplexes using fluorescence spectroscopy - Silva, J. P. Neves (2008)
Lipoplexes are commonly used as delivery systems in vitro and in vivo, the role of a neutral lipid as helper being of extreme importance in these systems. Cationic liposomes composed of dioctadecyldimethylammonium bromide (DODAB) with monoolein (MO) as a helper, at different molar ratios (1:2; 1:1 and 1:0.5) were prepared, and subsequently titrated to DNA. The structural and physicochemical properties of the lipid/DNA complexes were assessed by Ethidium Bromide (EtBr) exclusion, 90º Static Light Scattering (90º SLS) assays and Fluorescence Resonance Energy Transfer (FRET). In EtBr exclusion assays, the steady-state fluorescence spectra of EtBr were decomposed into the sum of two lognormal emissions, emanating from two different environments – H2O and DNA, and the effect of charge ratio (+/-) was observed. 90º SLS assays gave an important contribution, detecting size variations in systems with different MO fractions on the lipoplexes. In FRET assays, 2-(3-(diphenylhexatrienyl)propanoyl)-1-hexadecanoyl-sn-glycero-3-phosphocholine (DPH-HPC) was used as donor and EtBr as acceptor. The DNA component previously calculated by EtBr exclusion, was used to determine the energy transfer efficiency, as an indirect measurement of the lipoplexes structural and physicochemical properties. Our results demonstrate that the inclusion of monoolein in the cationic liposomes formulation significantly modifies the rate of DNA complexation, being DODAB:MO (1:1) the system with higher DNA condensation efficiency.